Implementation of automated information systems into the work of the certification body of the federal state budgetary institution «Scientific Centre for Expert Evaluation of Medicinal Products» of the Ministry of Health of the Russian Federation - V. A. Petrosyants; V. N. Kotikov; E. A. Soloviev; N. A. Korobeynikova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article describes the system of electronic document management related to the certification of medicinal immunobiological products (MIBP) in the Scientific Centre for Expert Evaluation of Medicinal Products», as well as historical aspects of its development. It also provides a brief description of CALS - the resources introduced into the expert institution’s activities, which are necessary for maintaining the life cycle of medicinal products. It specifies the main tasks that could be solved with the help of the IS «Document flow related to certification of MIBPs». The article enumerates the main development stages of the information system and its functional capabilities. It contains a review of certain modules of the IS «Document flow related to certification of MIBPs», implemented to meet modern standards of information security. It also summarizes the findings of the development of the IS «Document flow related to certification of MIBPs». The prospects of using the IS «Document flow related to certification of MIBPs» in the expert and scientific activities of the institution are also provided.